Internet access at home and varied usage as determinants of South African students’ mathematics performance - Saal, Petronella Elize; Hannan, Sylvia; Mbanda, Vandudzai (Indonesian Journal of Science and Mathematics Education, 2025)
Mathematics plays a crucial role in economic and technological advancement; however, disparities in internet access can affect students' academic performance. This study examines the relationship between home internet access, varied internet usage, and mathematics achievement among Grade 9 students in South Africa, using data from the 2019 Trends in International Mathematics and Science Study (TIMSS). Employing descriptive statistics and multi-level modeling, the findings reveal that less than half of the students had internet access at home, with significant disparities based on school socioeconomic status. Students with internet access who used it to find information, articles, or tutorials for mathematics performed better than those without access. However, students who relied on the internet to access textbooks, course materials, assignments, or teacher communication demonstrated lower performance than their peers. This study highlights the impact of the digital divide on education and suggests policy interventions to enhance equitable access to educational resources. The findings imply that addressing this gap through targeted digital infrastructure investments and ICT training for both students and teachers can improve mathematics achievement and promote educational equity.